Psikoedukasi Kesiapan Kerja Siswa Kelas XII SMA Muhammadiyah 2 Bobotsari Purbalingga - Satata, Dian Bagus Mitreka; Meilani, Eka Rizki; Huda, Tesa Nurul (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
In the current era of the Fourth Industrial Revolution, various phenomena indicate that many prospective workers face difficulties in securing employment after completing their secondary or vocational education. This suggests that many students are not yet adequately prepared for the workforce. The purpose of this training is to help students develop sufficient work readiness upon completing their schooling through structured training. The training method employs psychoeducation using a service-learning approach, which emphasizes practical aspects and is based on the concept of experiential learning. The results of the psychoeducation contribute to changes in the perspectives of XII grade students at Muhammadiyah 2 High School Bobotsari, helping them to set goals for their future after completing their education.